Integrasi Materi Otentik dalam Kegiatan Ekstra Kurikuler Bahasa Inggris SD - Rina Wahyu Setyaningrum; Fardini Sabilah (Universitas Brawijaya, 2015)
The newest 2013 Curriculum in Indonesia puts English as an extracurricular activity. It is an irony regarding the long process of elevating English as a foreign language accepted worldwide. As now English is an extra- curricular activity, there is no standard to achieve. That aforementioned fact requires that English practitioners seek for solutions. One of the proposed solutions is by involving non-English teachers from all grades in Primary School in managing English extracurricular activities by integrating authentic materials. The steps, drawn from the qualitative data collecting technique, incorporated the forms of training all teachers at primary schools, writing a guideline in conducting extra-curricular activities by integrating authentic materials, constructing the guideline advisory processes, and presenting the guideline in the form of lesson plans. The results of this current study propose insightful description on how English extra-curricular activities are supposed to be properly and well conducted.Keywords: Curriculum 2013, authentic materials, English, Primary Schools